Interplays Between Mantle Flow and Slab Pull at Subduction Zones in 3D. Issue 5 (20th May 2021) - Guillaume, B.; Funiciello, F.; Faccenna, C.
Abstract: The understanding of the interactions between subduction‐induced mantle flow and background mantle flow (being global or regional) remains incomplete despite its potential impact on subduction dynamics and associated deformation. Here we present the results of three‐dimensional laboratory models of subduction zones at the scale of the upper mantle in which we systematically vary the plate's width and trench perpendicular background mantle flow. In particular, we test different mantle flow magnitudes and directions of flow, and evaluate their impact on the slab geometry in the vertical plane, trench shape evolution, and the superficial horizontal mantle deformation. While the chosen viscosity ratio between the convective mantle and the subducting plate in our models (∼100) is favorable to the deformation of the slab through mantle displacement, we show that the geometry of the slab in the vertical plane is only marginally affected by the imposed background flow. Instead, the background flow has a larger impact on the horizontal kinematics and deformation of the trench. It reduces along‐trench variations of trench kinematics, which in turn decreases trench curvature, and it largely disturbs the pattern of mantle deformation at slab edges, inhibiting the development of toroidal cells. We also show that the thickness of the convective layer (here, the upper mantle) controls the toroidal component of the mantle flow and the length scale of trench curvature for large subduction zones. Plain Language Summary: The convective mantle and the lithospheric plates interact on geological time scales to produce plates' displacement and deformation. However, the nature of their interactions is still poorly understood, in particular at subduction zones. Here, we test with new three‐dimensional laboratory models of subduction, the effect of imposing a trench perpendicular background mantle flow, whose origin could be regional or global, on subduction dynamics. We show that the geometry of the slab in the vertical plane, which would define the Wadati‐Benioff zone, is only slightly affected by the magnitude and direction of the imposed flow. These results are at odds with previous two‐dimensional studies that, by definition, do not allow mantle to flow around slab edges, confirming that the toroidal component of mantle flow is a crucial component of subduction systems that needs to be taken into account while modeling subduction zones. We also show that the imposed background flow controls the velocity at which trenches move horizontally, which in turn impacts the shape of the subduction trench, and the way the mantle deforms around and above the subducting plate. Key Points: Trench‐perpendicular horizontal mantle flow strongly controls trench kinematics and curvature as well as mantle deformation around the slab Trench‐perpendicular horizontal mantle flow only marginally affects the slab geometry in the vertical plane Curvature at subduction margins is independent of slab width and scales with the thickness of the convective layer